2019
DOI: 10.1038/s41598-019-49299-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological mTOR targeting enhances the antineoplastic effects of selective PI3Kα inhibition in medulloblastoma

Abstract: Despite recent advances in the treatment of medulloblastoma, patients in high-risk categories still face very poor outcomes. Evidence indicates that a subpopulation of cancer stem cells contributes to therapy resistance and tumour relapse in these patients. To prevent resistance and relapse, the development of treatment strategies tailored to target subgroup specific signalling circuits in high-risk medulloblastomas might be similarly important as targeting the cancer stem cell population. We have previously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…The antineoplastic effects of alpelisib can be enhanced by pharmacological mTOR inhibition in breast cancer 34 , 55 and medulloblastoma 63 . Here we provide evidence that also in GSCs concomitant mTOR inhibition potentiates the antineoplastic effects of PI3Kα inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The antineoplastic effects of alpelisib can be enhanced by pharmacological mTOR inhibition in breast cancer 34 , 55 and medulloblastoma 63 . Here we provide evidence that also in GSCs concomitant mTOR inhibition potentiates the antineoplastic effects of PI3Kα inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…With that said, simultaneous targeting of SMO and GLI has been shown to provide synergistic inhibitory effects on various cancers, including multiple myeloma [ 250 , 251 ], medulloblastoma [ 252 ], and glioblastoma [ 253 ]. Additionally, a combination of SMO inhibitors with inhibitors targeting other oncogenic targets, such as PI3K/AKT/mTOR [ 254 , 255 , 256 , 257 ], EGFR [ 258 ], DNA methyltransferases [ 83 ], and interleukin 6 [ 259 ], resulted in synergistic inhibition of cancer cell growths. Such combinations included the use of SMO or GLI inhibitors with drugs targeting oncogenic drivers of noncanonical GLI activation, which allows for the simultaneous targeting of compensatory noncanonical GLI activation and other Hh-unrelated key cancer targets.…”
Section: Current Challenges and Future Perspective For Using Smo/gli Inhibitors In Clinical Settingsmentioning
confidence: 99%
“…and PI3K inhibition has demonstrated efficacy against medulloblastoma cells and tumors [131,130]. In preclinical in vivo studies, this effect was enhanced with concurrent mTOR inhibition, and the percentage of stem cells was decreased with combined PI3K/ mTOR inhibition [132]. Further studies have shown that Akt inhibition with perifosine can re-sensitize medulloblastoma nestin + stem cells to radiation treatment [129].…”
Section: Targeted Agentsmentioning
confidence: 99%